The Effect of Child Care Costs on the Labor Force Participation and Welfare Recipiency of Single Mothers: Implications for Welfare Reform - Rachel Connelly; Jean Kimmel (W.E. Upjohn Institute for Employment Research, 2001)
This paper considers the effect of child care costs on two labor market outcomes for single mothers whether to participate in the labor market and whether to receive welfare. Hourly child care expenditures are estimated for all women in the sample (using data drawn from the 1992 and 1993 panels of the SIPP), whether or not they are currently using nonmaternal child care. These expenditures are then included as an independent variable predicting the probability of welfare recipiency and the probability of labor force participation. Results show a substantial positive effect of child care costs on welfare recipiency, with a child care price elasticity of welfare recipiency equaling 0.28. The estimated child care price elasticity of employment equals -0.76, showing that controlling for the welfare choice does not reduce the price elasticity of employment found in other studies. Simulations based on these data from 1994 show that welfare recipiency is reduced by approximately one-third and employment increased by approximately 50 percent when child care expenditures are subsidized by 50 percent not a large subsidy considering that the weekly expenditure on child care was about 58. While this study relies on data collected prior to the 1996 federal welfare reform that block grants welfare dollars to the states, the results show the importance of child care to both the employment and welfare outcomes and imply that policymakers will continue to need to address child care concerns as state welfare policy evolves.
Keywords: I3; J2; J6; 330; welfare; welfare reform; single mothers; childcare; Kimmel